2014
DOI: 10.1208/s12249-014-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process and Formulation Parameters on Dissolution and Stability Characteristics of Kollidon® VA 64 Hot-Melt Extrudates

Abstract: Abstract. The objective of the present study was to investigate the effects of processing variables and formulation factors on the characteristics of hot-melt extrudates containing a copolymer (Kollidon® VA 64). Nifedipine was used as a model drug in all of the extrudates. Differential scanning calorimetry (DSC) was utilized on the physical mixtures and melts of varying drug-polymer concentrations to study their miscibility. The drug-polymer binary mixtures were studied for powder flow, drug release, and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The drawbacks associated with HME are usually related to the exposure of the product to high processing temperatures for relatively long residence times. Processing of APIs that have high melting points or are thermally labile continues to be a challenge due to energy input required during HME to produce an amorphous final product (17,18). Additionally, higher molecular weight polymers that may be effective for stabilizing the amorphous drug may be too viscous for processing via HME due to high torque loads, requiring the use of plasticizers that decrease the final product glass transition temperature (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks associated with HME are usually related to the exposure of the product to high processing temperatures for relatively long residence times. Processing of APIs that have high melting points or are thermally labile continues to be a challenge due to energy input required during HME to produce an amorphous final product (17,18). Additionally, higher molecular weight polymers that may be effective for stabilizing the amorphous drug may be too viscous for processing via HME due to high torque loads, requiring the use of plasticizers that decrease the final product glass transition temperature (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Assay of MA in the extrudates confirmed that the extrudates were chemically stable, with no drug degradation when analyzed for the drug content after storage duration (>99%, within 1% difference) 37 . DSC analysis demonstrated that the drug remained in an amorphous form, as the corresponding endothermic peak was not present after 6 months of storage (Figure 11-a & 12-a).…”
Section: Resultsmentioning
confidence: 69%
“…As expected, CE showed a low flowability (=49), proving its poor flow capacity ( Table 2 ). Meanwhile, HME extrudates showed flowability in the range of 71–88, demonstrating a remarkable improvement of this property, which enables this processed natural product to be used in direct compression of tablets or to fill capsules, without any additional processing [ 28 ].…”
Section: Resultsmentioning
confidence: 99%